CIAT/WLE and partners supported the Amhara region in Ethiopia to invest more than USD 10 Million for the construction of a dam for drinking water and catchment management - CGIAR Research Program on Water, Land and Ecosystems (2019)
CIAT/WLE, Africa RISING (AR) and Mekelle University (MU) team developed feasibility report based on which detailed feasibility study was conducted. Now a Contractor has started building the dam. CIAT, AR, MU are now collaborating with national and international partners to develop detailed integrated watershed management plan to tackle dam siltation.